Short duration of untreated psychosis enhances negative symptom remission in extended early intervention service for psychosis. (23rd April 2019) - Dama, M.; Shah, J.; Norman, R.; Iyer, S.; Joober, R.; Schmitz, N.; Abdel‐Baki, A.; Malla, A.
Abstract : Objective: To test whether duration of untreated psychosis (DUP) < 3 months, recommended by the World Health Organization/International Early Psychosis Association, enhances the effects of an extended early intervention service (EEIS) on symptom remission. Method: We examined data from a randomized controlled trial in which patients who received 2 years of treatment in EIS for psychosis were subsequently randomized to either 3 years of EEIS or 3 years of regular care (RC). Using a DUP cut‐off ≤ 12 weeks (approximately < 3 months), patients were split into two groups. Length of positive, negative and total symptom remission were the outcomes. Results: Patients ( N = 217) were mostly male (68%) with schizophrenia spectrum disorder (65%); 108 (50%) received EEIS (58 had DUP ≤12 weeks; 50 had DUP >12 weeks). Interaction between treatment condition (EEIS vs. RC) and DUP cut‐off ≤ 12 weeks was only significant in multiple linear regression model examining length of negative symptom remission as the outcome (adjusted β = 36.88 [SE = 15.88], t = 2.32, P = 0.02). EEIS patients with DUP ≤12 weeks achieved 25 more weeks of negative symptom remission than EEIS patients with DUP >12 weeks. Conclusion: Having a short DUP may be critical in deriving long‐term benefits from EIS for psychosis, including EEIS settings. This work empirically supports policy recommendations of reducing DUP <3 months.